The Effects of Different Desertification Control Measures on Soil Physicochemical Properties and Enzyme Activities in Sand Blocking and Fixation Zone - TIAN Yongsheng; MA Rui; LIU Teng; MA Yanjun (Shuitu Baochi Xuebao)
［Objective］ To explore the effects of different sand control measures on soil physicochemical properties and enzyme activity in sand blocking and stabilization zones, and their relationships, in order to provide technical support for measure selection and benefit evaluation. ［Methods］ Using mobile sand dunes and Haloxylon ammodendron(CK) as the control group, and ecological cushion sand barrier+Haloxylon ammodendron (ES), nylon mesh sand barrier+H. ammodendron (NS), woven bag sand barrier+H. ammodendron (WS), grass square grid sand barrier+H. ammodendron (GS), and clay sand barrier+H. ammodendron (CS) as the test groups, physical and chemical properties and enzyme activities of soil within 0~60 cm depth for six different sand control measures were analyzed. ［Results］ Compared with CK, there were significant changes in soil physicochemical properties and enzyme activities among the other five different sand control measures. 1) Within the depth range of 0~60 cm, there was no significant change in soil pH, but soil moisture content (SWC) increased with increasing soil depth. The mass fractions of soil organic carbon (SOC), total nitrogen (TN), total phosphorus (TP), and total potassium (TK) decreased with increasing soil depth. Compared with CK, the other five different sand control measures had a significant increase in soil nutrient content, with NS showing the most significant increase. 2) Under different desertification control measures, soil enzyme activities of NS measure were the highest, followed by that of GS, and that of CS were the lowest. Within the depth range of 0~60 cm, soil enzyme activities showed a decreasing trend.3) There were significant correlations between soil physicochemical properties and soil enzyme activities. The contribution of soil physicochemical properties to soil enzyme activities varied under different desertification control measures, and soil enzyme activities were mainly influenced by TK, SOC, and SWC. ［Conclusion］ Five different sand control measures have varying degrees of promoting effects on soil physicochemical properties and enzyme activities, among which NS sand control measures have the best ecological benefits and long-term stability.